Earnings, adaptation and equity value. - Burgstahler, David C.; Dichev, Ilia D. (The Accounting Review, 1997)
Abstract This paper develops and tests an option-style valuation model, whose main prediction is that equity value is a convex function of both earnings and book value, where the function depends on the relative values of earnings and book value. Earnings provides a measure of how the firm's resources are currently used. Book value provides a measure of the value of the firm's resources, independent of how the resources are currently used. When the ratio earnings/book value is high, the firm is likely to continue its current way of using resources, and earnings is the more important determinant of equity value. When earnings/book value is low, the firm is more likely to exercise the option to adapt its resources to a superior alternative use, and book value becomes the more important determinant of equity value. Evidence from a variety of empirical specifications is consistent with the convexity prediction.